Novel disease state model finds most juvenile green turtles develop and recover from fibropapillomatosis. Issue 3 (23rd March 2022) - Kelley, Jake R.; Kelley, Kayla L.; Savage, Anna E.; Mansfield, Kate L.
Abstract: Fibropapillomatosis (FP) is a sea turtle disease characterized by benign tumor development on the skin, eyes, and/or internal organs. It primarily affects juvenile green turtles ( Chelonia mydas ) in coastal foraging sites. The Indian River Lagoon (IRL), Florida, USA, is a coastal green turtle foraging site where the observed FP annual rate averaged 49% between 1983 and 2018. While FP is no longer considered a major cause of sea turtle mortality and most individuals fully recover, the overall dynamics of this disease are poorly understood because prior disease history is unknown for individuals without FP at capture time, and future disease outcome is unknown for individuals with FP at capture time. To better evaluate FP dynamics for green turtles in the IRL, we developed a hierarchical model for predicting disease state change. We used data from 4149 captures of 3700 individual green turtles captured in the IRL. The hierarchical disease state model contained two levels: Level 1 modeled whether an individual would develop FP, and Level 2 modeled disease state progression, including states for pre‐FP affliction, active FP affliction, and full recovery from FP. From the hierarchical model, we estimated 99.8% (95% credibility intervals 99.1%–100%) of juvenile green turtles in the IRL developed FP, indicating that nearly every individual in the IRL is affected by this disease. The model also suggested that turtles quickly developed FP upon recruitment to the IRL and then recovered at different rates, with most completely recovering before emigrating from the IRL as they mature. This is the first analysis of long‐term sea turtle data suggesting nearly every turtle in an aggregation both develops and recovers from FP.